2018
DOI: 10.1063/1.5010956
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Fermi level by nin diamond junction for control of charge states of NV centers

Abstract: The charge-state control of nitrogen-vacancy (NV) centers in diamond is very important toward its applications because the NV centers undergo stochastic charge-state transitions between the negative charge state (NV À ) and the neutral charge state (NV 0 ) of the NV center upon illumination. In this letter, engineering of the Fermi level by a nin diamond junction was demonstrated for the control of the charge state of the NV centers in the intrinsic (i) layer region. By changing the size (d) of the i-layer reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 33 publications
(50 reference statements)
1
28
0
Order By: Relevance
“…Based on the work of Groot-Berning et al (2014), surface termination should provide enhanced charge-state stability to a depth of at least 60 nm, and possibly farther (Malinauskas et al, 2008;Santori et al, 2009). The chargestate efficiency ζ can also be controlled electrically (Grotz et al, 2012;Kato et al, 2013;Hauf et al, 2014;Schreyvogel et al, 2014Schreyvogel et al, , 2015Karaveli et al, 2016;Forneris et al, 2017;Murai et al, 2018). Because diamond is an approximately 5.47 eV wide band gap insulator (Wort and Balmer, 2008), Collins (2002) contends that an NV center's charge-state depends less on the position of the Fermi level and more on the distance to the nearest charge donor.…”
Section: Nonoptical Effects On Nv Charge-state Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the work of Groot-Berning et al (2014), surface termination should provide enhanced charge-state stability to a depth of at least 60 nm, and possibly farther (Malinauskas et al, 2008;Santori et al, 2009). The chargestate efficiency ζ can also be controlled electrically (Grotz et al, 2012;Kato et al, 2013;Hauf et al, 2014;Schreyvogel et al, 2014Schreyvogel et al, , 2015Karaveli et al, 2016;Forneris et al, 2017;Murai et al, 2018). Because diamond is an approximately 5.47 eV wide band gap insulator (Wort and Balmer, 2008), Collins (2002) contends that an NV center's charge-state depends less on the position of the Fermi level and more on the distance to the nearest charge donor.…”
Section: Nonoptical Effects On Nv Charge-state Efficiencymentioning
confidence: 99%
“…Introduction of electron donors other than nitrogen into diamond might appear to be a promising avenue for increasing the NV charge-state efficiency. For example, phosphorus (Groot-Berning et al, 2014;Doi et al, 2016;Murai et al, 2018), with a donor level 0.6 eV below the conduction band (Katagiri et al, 2004), is a shallower donor than nitrogen, which lies 1.7 eV below the conduction band (Farrer, 1969;Wort and Balmer, 2008). However, creating n-doped diamond through the introduction of phosphorus has proven difficult (Kalish, 1999), as phosphorus doping is correlated with the introduction of a deep acceptor tentatively identified as the phosphorus vacancy (PV) (Jones, Lowther, and Goss, 1996).…”
Section: Nonoptical Effects On Nv Charge-state Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the detrimental impact of charge state instability on spin polarization [13,17], and consequently on the sensing capabilities of NV centers, a clear understanding of charge dynamics of NV ensembles is lacking. * rakshyakar.giri@iit.it Attempts to control the charge states of NVs by manipulating the Fermi level are reported in the literature [11,[18][19][20][21][22]. It was demonstrated that an ensemble of NV centers could be stable enough to be used as a charge based data storage medium [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Groot-Berning et al have clearly shown the effect of co-doping in implanted diamond films [170] as illustrated in figure 7(b). Fermi level tuning can also be achieved with insitu doped CVD diamond films [171] allowing a fine control over NV's charge state. Intentional doping of diamond by phosphorous during CVD growth is however particularly challenging due to the low doping efficiency of this element into the diamond while n-type conductivity is limited by compensating defects and high activation energy (0.6 eV) [172].…”
Section: Controlling Nvs Charge Statementioning
confidence: 99%